How to design cryptocurrency value and how to secure its sustainability in the market - Soonduck Yoo (Journal of Risk and Financial Management, 2021)
The purpose of this study is to analyze the contents of cryptocurrency value design based on adaptability to the current market. It is also intended to provide a method of issuing cryptocurrency before its creation, and an operation method afterwards. Activities before the creation of cryptocurrency must determine desirable behaviors and rewards to create value, and suggest countermeasures to prevent participants from engaging in undesirable behaviors. After the creation of a cryptocurrency, it is necessary to propose a method to induce scarcity and increase demand so that the value of the generated cryptocurrency can be sustained. To observe this, we looked at the contents of the value design of the eight types of cryptocurrencies currently in use in the market. Some cryptocurrencies, such as Bitcoin, are choosing mining as a reward, to secure scarcity for maintaining the value of cryptocurrency, limiting the amount of issuance, and burning the already issued cryptocurrency in the market. Also, increasing demand helps maintain the value of cryptocurrency. This study can contribute to supporting the growth of a healthy cryptocurrency market through cryptocurrency-related research.
Keywords: 330; virtual currency; Bitcoin; blockchain technology; cryptocurrency value; sustainability